An MBSE Approach to Support Organisational Reform of the Royal Australian Navy. Issue 1 (28th October 2015) - Do, Quoc; Gahan, Malcolm; Davidson, Colin
Abstract: This paper presents a unique MBSE approach to enterprise modelling using a combination of IDEF0 functional modelling method. This approach has been applied to the modelling of the engineering and administrative processes of the Royal Australian Navy (RAN). The developed model is named Materiel Seaworthiness Functional Master Set (MS FMS). Importantly, the MS FMS initiative is being driven from the top‐down by the Head of Navy Engineering, Rear Admiral Mick Uzzell AM, so that he can be assured that all organisational entities in the large and complex environment of Navy, Defence Groups and Industry are performing the right functions in a coordinated way to continuously deliver seaworthy materiel (i.e. ships, submarines and support items). To further the quest to balance effective delivery with efficient resource allocation, an analytical capability using the well established Multi‐attribute Value Analysis (MVA) method is being piloted, and is named the FMS Traffic Light System which aims to facilitate "what if" analysis, ascertain functional health status, and inform high‐level organisational resource allocation and strategic planning.